A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Optimizing Perovskite Thin-Film Parameter Spaces with Machine Learning-Guided Robotic Platform for High-Performance Perovskite Solar Cells - Zhang, Jiyun; Liu, Bowen; Liu, Ziyi; Wu, Jianchang; Arnold, Simon; Shi, Hongyang; Osterrieder, Tobias; Hauch, Jens; Wu, Zhenni; Luo, Junsheng; Wagner, Jerrit; Berger, Christian; et al. (Advanced Energy Materials, 2023)
Simultaneously optimizing the processing parameters of functional thin films remains a challenge. The design and utilization of a fully automated platform called SPINBOT is presented for the engineering of solution-processed functional thin films. The SPINBOT is capable of performing experiments with high sampling variability through the unsupervised processing of hundreds of substrates with exceptional experimental control. Through the iterative optimization process enabled by the Bayesian optimization (BO) algorithm, the SPINBOT explores an intricate parameter space, continuously improving the quality and reproducibility of the produced thin films. This machine learning (ML)-guided reliable SPINBOT platform enables the acceleration of the optimization process of perovskite solar cells via a simple photoluminescence characterization of films. As a result, this study arrives at an optimal film that, when processed into a solar cell in an ambient atmosphere, immediately yields a champion power conversion efficiency (PCE) of 21.6% with satisfactory performance reproducibility. The unsealed devices retain 90% of their initial efficiency after 1100 h of continuous operation at 60–65 °C under metal-halide lamps. It is anticipated that the integration of robotic platforms with the intelligent algorithm will facilitate the widespread adoption of effective autonomous experimentation to address the evolving needs and constraints within the materials science research community.
CRIS-Team Scopus Importer:2023-11-10
Keywords: closed-loop optimization; efficient and stable devices; machine learning; manufacturing optimization; perovskite thin films; PL characterization; robotic platform

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15